Method for estimating oxygen release amount of ternary lithium ion battery positive electrode material

By combining experimental testing and theoretical analysis, the oxygen release amount is calculated based on the residual lithium content of the positive electrode material of the ternary lithium-ion battery, which solves the problem of difficult estimation of the oxygen release amount in the prior art, and the accurate measurement of the oxygen release amount at high temperatures is achieved. Reduces costs and risks.

CN119223807APending Publication Date: 2024-12-31CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411476522.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively estimate the oxygen release amount of positive electrode materials of ternary lithium-ion batteries at high temperatures, resulting in poor thermal stability and increasing the risk of fire and explosion.

Method used

Through a combination of experimental testing and theoretical analysis, the oxygen release amount is calculated based on the residual lithium content in the positive electrode material of the ternary lithium-ion battery, including determining the molar mass, theoretical capacity, actual capacity ratio and oxygen release during the phase change process, including determining the molar mass, theoretical capacity, actual capacity ratio and oxygen release during the phase transition. .

Benefits of technology

It realizes accurate, fast and low-cost estimation of oxygen release without large-scale instruments, reducing the cost of procurement and external inspection of analytical instruments and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119223807A_ABST
    Figure CN119223807A_ABST
Patent Text Reader

Abstract

The invention discloses a method for estimating the oxygen release amount of a ternary lithium ion battery positive electrode material. The method comprises the following steps: determining the molar mass according to the chemical formula of the ternary lithium ion battery positive electrode material; substituting into a theoretical capacity calculation formula to calculate the theoretical capacity of the ternary lithium ion battery positive electrode material; preparing a ternary lithium ion battery positive electrode material; assembling a positive electrode half battery of the ternary lithium ion battery positive electrode material to determine the actual capacity of the ternary lithium ion battery positive electrode material; determining the proportion of residual lithium ions in the material according to the ratio of the actual capacity to the theoretical capacity; and substituting the proportion of the remaining lithium ions into the two phase transformation chemical equations, and calculating to obtain the oxygen release amount. According to the method, the oxygen release amount in the phase change process of the material is calculated according to the residual lithium content in the ternary lithium ion battery positive electrode material by means of combining experimental test and theoretical analysis, and the method has the characteristics of accurate test and low test cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for estimating the oxygen release amount of a positive electrode material of a ternary lithium ion battery. Background Art

[0002] As the market demand for the energy density of lithium-ion batteries gradually increases, the nickel-cobalt-manganese ternary series of materials are widely used in power batteries for new energy vehicles. Therefore, in addition to electrochemical performance, thermal safety performance is also an important factor affecting its further development and application. Understanding the internal transformation of the material itself and its thermal contribution will help to determine its thermal contribution and further reveal the thermal runaway mechanism. In general, the structural changes on the surface and inside of the material are directly related to its composition. Severe lithium ion desorption and oxygen evolution can put the material in a thermodynamic metastable state, and these changes are also intuitively reflected in the reduced thermal stability of the electrode material. Especially during high-level delithiation or heating, oxygen release plays a core role in affecting the safety characteristics of ternary lithium-ion battery cathode materials, because it can react with organic electrolytes, resulting in poor thermal stability of the system and increased possibility of thermal runaway. However, how to estimate the amount of oxygen released by the thermally induced ternary lithium-ion battery cathode material after delithiation has not been disclosed in literature journals and related patent documents. Summary of the invention

[0003] The thermal stability of the positive electrode material of a ternary lithium-ion battery in a highly de-lithiated state is extremely poor. It is easy to decompose and produce oxygen at high temperatures, resulting in severe oxidation of the electrolyte on the positive electrode surface, releasing a large amount of heat, and in severe cases inducing serious fire and explosion accidents in the battery. The purpose of the present invention is to provide a method for estimating the oxygen release amount of the positive electrode material of a ternary lithium-ion battery. The method calculates the oxygen release amount of the material phase change process according to the residual lithium content in the positive electrode material of the ternary lithium-ion battery by combining experimental testing with theoretical analysis, and has the characteristics of accurate testing and low testing cost.

[0004] A method for estimating the oxygen release amount of a ternary lithium-ion battery positive electrode material comprises: determining the molar mass through the chemical formula of the ternary lithium-ion battery positive electrode material; substituting the molar mass into a theoretical capacity calculation formula to calculate the theoretical capacity of the ternary lithium-ion battery positive electrode material; preparing the ternary lithium-ion battery positive electrode material; assembling a positive electrode half-cell of the ternary lithium-ion battery positive electrode material to determine the actual capacity of the ternary lithium-ion battery positive electrode material; thereby determining the proportion of residual lithium ions in the material according to the ratio of the actual capacity to the theoretical capacity; and substituting the proportion of residual lithium ions into two phase transition chemical reaction equations to calculate the oxygen release amount.

[0005] After charging, the ternary positive electrode material will lose a certain amount of lithium ions and become structurally unstable. After heating, a phase transition process from layered structure to spinel structure and rock salt structure will occur, accompanied by the release of oxygen. The molar number of oxygen released during the phase change process is calculated by the change in the valence state of transition metal elements between ternary materials with different crystal structures.

[0006] Furthermore, the chemical formula of the positive electrode material of the ternary lithium-ion battery is LiNi x Co y Mn z O2.

[0007] Furthermore, the method for estimating the oxygen release amount of the positive electrode material of the ternary lithium-ion battery includes:

[0008] The first step is to calculate the molar mass of the material according to the molar ratio of the five elements of lithium, nickel, cobalt, manganese and oxygen in the selected ternary lithium-ion battery positive electrode material: M=MLi+xMNi+yMCo+zMMn+MO×2, wherein M represents the molar mass of the ternary lithium-ion battery positive electrode material, g / mol; MLi represents the molar mass of lithium, g / mol; MNi represents the molar mass of nickel, g / mol; MCo represents the molar mass of cobalt, g / mol; MMn represents the molar mass of manganese, g / mol; MO represents the molar mass of oxygen, g / mol; x, y, z represent the molar ratios of nickel, cobalt and manganese, respectively, x+y+z=1.

[0009] The second step is to calculate the theoretical specific capacity of the selected ternary lithium-ion battery positive electrode material according to the formula: Q0 = F × 1000 / M,

[0010] Where Q0 represents the theoretical specific capacity, mAh / g; F represents the Faraday constant, 26.801Ah / mol;

[0011] M represents the molar mass of the cathode material of the ternary lithium-ion battery, g / mol; M represents the molar mass of the cathode material of the ternary lithium-ion battery, g / mol;

[0012] The third step is to mix the nickel-cobalt-manganese ternary positive electrode material with the conductive agent and the binder in a mass ratio, add N-methylpyrrolidone (NMP), stir and mix thoroughly to form a uniform positive electrode slurry and evenly coat it on a 15 μm aluminum foil, and then dry it in a blast drying oven to obtain a positive electrode sheet;

[0013] Step 4: Use the above-mentioned positive electrode sheet as the positive electrode, the metal lithium sheet as the negative electrode, Celgard 2500 as the separator, add electrolyte, and assemble into a button-type half-cell with a battery model of CR2032 in a glove box;

[0014] The fifth step is to determine the actual charge and discharge specific capacity of the positive electrode material of the ternary lithium-ion battery within the set voltage range by charging and discharging the positive electrode half-cell for three cycles at a current of C / 20 within the set voltage range;

[0015] The sixth step is to determine the proportion of remaining lithium ions in the positive electrode material by using the ratio of the actual specific capacity of the nickel-cobalt-manganese ternary half-battery to the theoretical specific capacity of the positive electrode material of the ternary lithium-ion battery used;

[0016] In the seventh step, the proportion of remaining lithium ions is substituted into the two phase transition chemical reaction equations, and the oxygen release amounts in the transformation process from layered structure to spinel structure and the transformation process from spinel structure to rock salt structure are calculated respectively according to the change in valence. The sum of the release amounts in the two processes is the total oxygen release amount.

[0017] Furthermore, in step 1, the positive electrode material of the ternary lithium-ion battery is selected from LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.4 Co 0.4 Mn 0.2 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2, and LiNi 0.8 Co 0.1 Mn 0.1 Any of O2.

[0018] Furthermore, in the step three, the coating thickness of the positive electrode material on the aluminum foil is any one of 100 μm, 150 μm, 200 μm and 400 μm.

[0019] Furthermore, in the step three, the coating thickness of the positive electrode material on the aluminum foil is any one of 100 μm, 150 μm, 200 μm and 400 μm.

[0020] Furthermore, in step three, the binder is one or more combinations of polyvinylidene fluoride and carboxylated polyvinylidene fluoride.

[0021] Furthermore, in step three, the conductive agent is one or more combinations of carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene.

[0022] Furthermore, in the step three, the mass ratio of the nickel-cobalt-manganese ternary positive electrode material to the conductive agent and the binder in the positive electrode plate is any one of 8:1:1, 90:5:5 and 92:4:4.

[0023] Furthermore, in step three, the drying conditions in the air drying oven are: 100-130° C., 10-15 h.

[0024] Furthermore, in step seven, the phase transformation chemical reaction equation of the nickel-cobalt-manganese ternary positive electrode material is:

[0025] Li a [M (4-a)+ ] 1.0 O2 (layered structure) →

[0026]

[0027] Where M represents Ni x Co y Mn z ; The layered structure can be represented as LiMO2, the spinel structure can be represented as (Li+M)3O4, and the rock salt structure can be represented as (Li+M)O;

[0028] a represents Li a Remaining lithium content in MO2;

[0029] b and c represent the amount of oxygen released during the phase transition.

[0030] Among them, the residual lithium content a depends on the ratio of the actual specific capacity to the theoretical specific capacity of different ternary lithium-ion battery positive electrode materials at a certain cut-off voltage.

[0031] Beneficial effects of the present invention:

[0032] Compared with the prior art, the present invention adopts the traditional electrode sheet manufacturing method and lithium ion battery assembly method, and adopts the valence analysis method to test and calculate the phase change process and oxygen release of the positive electrode material of the ternary lithium ion battery at high temperature without adding large instruments (such as ICP-AES, XRF and other large quantitative analysis instruments). The whole process is a routine experimental operation, and no large analytical instruments are introduced. At the same time, the whole test process has no difficult operation. Personnel with relevant experimental experience can independently complete the test and calculation according to the steps, and it has the characteristics of accurate test, rapid test and low test cost. It also has economic benefits: reducing the cost of purchasing analytical instruments and the cost of outsourcing testing. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a general flow chart of the method for estimating the oxygen release amount of the positive electrode material of a ternary lithium-ion battery. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification. The methods described are all conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.

[0035] It should be mentioned before discussing the exemplary embodiments in more detail that some exemplary embodiments are described as processes or methods depicted as flow charts. Although the flow charts describe the operations as sequential processes, many of the operations therein can be implemented in parallel, concurrently or simultaneously. In addition, the order of the operations can be rearranged. The process can be terminated when its operation is completed, but can also have additional steps not included in the accompanying drawings. The process can correspond to a method, function, procedure, subroutine, subprogram, etc.

[0036] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0037] In order to facilitate subsequent understanding, the overall inventive concept of the present invention is described here: Figure 1 As shown, the method for estimating the oxygen release amount of the positive electrode material of a ternary lithium-ion battery provided by the present invention includes:

[0038] Basic parameter calculation: Determine the molar mass through the chemical formula of the positive electrode material of the ternary lithium-ion battery;

[0039] Substitute the theoretical capacity calculation formula to calculate the theoretical capacity of the positive electrode material of the ternary lithium-ion battery;

[0040] Experimental data acquisition: Preparation of positive electrode materials for ternary lithium-ion batteries;

[0041] Assembling positive electrode half-cells of positive electrode materials for ternary lithium-ion batteries;

[0042] Determine the actual capacity of cathode materials for ternary lithium-ion batteries;

[0043] Calculation of residual lithium content in ternary materials: Determine the proportion of residual lithium ions in the material based on the ratio of actual capacity to theoretical capacity;

[0044] Calculation of oxygen release during phase transition: Substitute the remaining lithium ion ratio into the chemical reaction equations of the two phase transitions (layered structure → spinel structure; spinel structure → rock salt structure) to calculate the oxygen release.

[0045] This method combines experimental testing with theoretical analysis to calculate the amount of oxygen released during the phase change process of the material based on the remaining lithium content in the positive electrode material of the ternary lithium-ion battery. It has the characteristics of accurate testing and low testing cost.

[0046] Example 1

[0047] In this embodiment, the positive electrode material of the ternary lithium-ion battery is LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811),

[0048] The first step is to calculate the molar mass of the material according to the molar ratio of lithium, nickel, cobalt, manganese and oxygen in the selected ternary lithium-ion battery positive electrode material: M = MLi + xMNi + yMCo + zMMn + MO × 2,

[0049] Among them, M represents the molar mass of the positive electrode material of the ternary lithium-ion battery, g / mol; MLi represents the molar mass of lithium, g / mol; MNi represents the molar mass of nickel, g / mol; MCo represents the molar mass of cobalt, g / mol; MMn represents the molar mass of manganese, g / mol; MO represents the molar mass of oxygen:

[0050] First, the molar mass of NCM811 is:

[0051] M=6.941+58.693×0.8+58.933×0.1+54.94×0.1+15.999×2=97.28g / mol

[0052] In the formula, 6.941 is the molar mass of lithium;

[0053] 58.693 – the molar mass of nickel;

[0054] 58.933 – the molar mass of cobalt;

[0055] 54.94 – molar mass of manganese;

[0056] 15.999 – The molar mass of oxygen.

[0057] The second step is to calculate the theoretical capacity according to the formula: Q0 = F × 1000 / M. The theoretical specific capacity of NCM811 is:

[0058] Q0=26.801×1000 / 97.28=276mAh / g

[0059] Where, 26.801——Faraday constant, Ah / mol;

[0060] 97.28 – The molar mass of NCM811, g / mol.

[0061] When charged to 4.2 V, the capacity obtained on the charge-discharge cycler is the actual specific capacity of the battery under the test conditions, which is 171 mAh / g.

[0062] The third step is to make the positive electrode sheet of the positive electrode material of the ternary lithium-ion battery as follows:

[0063] LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of positive electrode material: acetylene black: polyvinylidene fluoride = 8:1:1. After mixing, N-methylpyrrolidone (NMP) is added, and the mixture is fully stirred to form a uniform positive electrode slurry and evenly coated on a 15μm thick aluminum foil with a coating thickness of 100μm. After drying in a blast drying oven at 120°C for 12h, the positive electrode sheet is obtained for use.

[0064] The fourth step is to prepare a nickel-cobalt-manganese ternary positive electrode half-cell. The specific steps are as follows:

[0065] The above-mentioned positive electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, Celgard 2500 was used as the separator, and commercial electrolyte was added to assemble a button-type half-cell with a battery model of CR2032 in a glove box.

[0066] Step 5: Battery testing steps are as follows:

[0067] The assembled button cell was left at room temperature (25°C) for 12 hours and then placed in a constant temperature battery cycler for cycling, with a charge and discharge voltage of 2.8 to 4.2 V. The battery was first charged and discharged for three cycles at a current of C / 20, and then charged to a cut-off voltage of 4.2 V at a current of C / 5.

[0068] The test procedure is: C / 20 constant current charging to 4.2V, then C / 20 discharge to 2.8V. After fully activating the electrode material, C / 5 constant current charging to a cut-off voltage of 4.2V is used, and then constant voltage charging is switched to fully delithiate the positive electrode material, with a cut-off current of C / 50.

[0069] When charged to 4.2 V, the capacity obtained on the charge-discharge cycler is the actual specific capacity of the battery under the test conditions, which is 171 mAh / g.

[0070] Step 6: The ratio of remaining lithium ions: (171 mAh / g) / (276 mAh / g)=62%.

[0071] Step 7: From the previous step, we can see that about 62% of lithium is extracted from NCM811, and about 38% of lithium remains in the material.

[0072] That is, a = 0.38. Then, by substituting the a value into the chemical equations of the two phase transition processes,

[0073] Li a [M (4-a)+ ] 1.0 O2(layered,R-3m)→

[0074]

[0075] Where M represents Ni x Co y Mn z ; The layered structure can be represented as LiMO2, the spinel structure can be represented as (Li+M)3O4, and the rock salt structure can be represented as (Li+M)O;

[0076] a represents Li a Remaining lithium content in MO2;

[0077] b and c represent the amount of oxygen released during the phase transition.

[0078] By balancing the chemical equation, the amount of oxygen released per mole of NCM811 in the two phase transitions can be obtained. The phase transition process can be summarized as follows:

[0079] Li 0.38 (Ni 0.8 Co 0.1 Mn 0.1 ) 3.62+ O2→Li 0.38 (Ni 0.8 Co 0.1 Mn 0.1 ) 3.30+ O 1.84 +0.08O2↑

[0080] Li 0.38 (Ni 0.8 Co 0.1 Mn 0.1 ) 3.30+ O 1.84 →Li 0.38 (Ni 0.8 Co 0.1 Mn 0.1 ) 2.38+ O 1.38 +0.23O2↑

[0081] In summary, at a cut-off voltage of 4.2 V, each mole of NCM811 releases 0.62 moles of lithium ions, leaving 0.38 moles of lithium ions in the material. During the two processes of transformation from layered structure to spinel structure and from spinel structure to rock salt structure, 0.08 moles and 0.23 moles of oxygen are released respectively.

[0082] The above embodiments are provided for persons familiar with the art to implement or use the present invention. Personnel familiar with the art can make various modifications or changes to the above embodiments without departing from the inventive concept of the present invention. Therefore, the protection scope of the present invention is not limited to the above embodiments, but should be the maximum scope of the innovative features mentioned in the claims.

Claims

1. A method for estimating the oxygen release amount of a ternary lithium-ion battery positive electrode material, characterized in that: include: Determine the molar mass by the chemical formula of the cathode material of the ternary lithium-ion battery; Substitute the theoretical capacity calculation formula to calculate the theoretical capacity of the positive electrode material of the ternary lithium-ion battery; Prepare positive electrode materials for ternary lithium-ion batteries; assemble positive electrode half-cells for positive electrode materials for ternary lithium-ion batteries to determine the actual capacity of positive electrode materials for ternary lithium-ion batteries; Therefore, the proportion of remaining lithium ions in the material is determined based on the ratio of actual capacity to theoretical capacity; the proportion of remaining lithium ions is substituted into the two phase transition chemical reaction equations to calculate the amount of oxygen released.

2. The method for estimating the oxygen release amount of a ternary lithium-ion battery positive electrode material according to claim 1, characterized in that: The chemical formula of the positive electrode material of the ternary lithium-ion battery is LiNi x Co y Mn z O2.

3. The method for estimating the oxygen release amount of a ternary lithium-ion battery positive electrode material according to claim 2, characterized in that: The method comprises: The first step is to calculate the molar mass of the material according to the molar ratio of lithium, nickel, cobalt, manganese and oxygen in the selected ternary lithium-ion battery positive electrode material: M = MLi + xMNi + yMCo + zMMn + MO × 2, Among them, M represents the molar mass of the positive electrode material of the ternary lithium-ion battery, g / mol; MLi represents the molar mass of lithium, g / mol; MNi represents the molar mass of nickel, g / mol; MCo represents the molar mass of cobalt, g / mol; MMn represents the molar mass of manganese, g / mol; MO represents the molar mass of oxygen, g / mol; x, y, z represent the molar ratios of nickel, cobalt and manganese, respectively, x+y+z=1. The second step is to calculate the theoretical specific capacity of the selected ternary lithium-ion battery positive electrode material according to the formula: Q0 = F × 1000 / M, Wherein, Q0 represents the theoretical specific capacity, mAh / g; F represents the Faraday constant, 26.801Ah / mol; M represents the molar mass of the positive electrode material of the ternary lithium-ion battery, g / mol; M represents the molar mass of the positive electrode material of the ternary lithium-ion battery, g / mol; The third step is to mix the nickel-cobalt-manganese ternary positive electrode material with the conductive agent and the binder in a mass ratio, add N-methylpyrrolidone (NMP), stir and mix thoroughly to form a uniform positive electrode slurry and evenly coat it on a 15 μm aluminum foil, and then dry it in a blast drying oven to obtain a positive electrode sheet; Step 4: Use the above-mentioned positive electrode sheet as the positive electrode, the metal lithium sheet as the negative electrode, Celgard 2500 as the separator, add electrolyte, and assemble into a button-type half-cell with a battery model of CR2032 in a glove box; The fifth step is to determine the actual charge and discharge specific capacity of the positive electrode material of the ternary lithium-ion battery within the set voltage range by charging and discharging the positive electrode half-cell for three cycles at a current of C / 20 within the set voltage range; The sixth step is to determine the proportion of remaining lithium ions in the positive electrode material by using the ratio of the actual specific capacity of the nickel-cobalt-manganese ternary half-battery to the theoretical specific capacity of the positive electrode material of the ternary lithium-ion battery used; In the seventh step, the proportion of remaining lithium ions is substituted into the two phase transition chemical reaction equations, and the oxygen release amounts in the transformation process from layered structure to spinel structure and the transformation process from spinel structure to rock salt structure are calculated respectively according to the change in valence. The sum of the release amounts in the two processes is the total oxygen release amount.

4. The method for estimating oxygen release of a ternary lithium-ion battery cathode material according to claim 3, characterized in that: In step 1, the positive electrode material of the ternary lithium-ion battery is selected from LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.4 Co 0.4 Mn 0.2 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2, and LiNi 0.8 Co 0.1 Mn 0.1 Any of O2.

5. The method for estimating oxygen release of a ternary lithium-ion battery cathode material according to claim 3, characterized in that: In the step three, the coating thickness of the positive electrode material on the aluminum foil is any one of 100 μm, 150 μm, 200 μm and 400 μm.

6. The method for estimating oxygen release of a ternary lithium-ion battery cathode material according to claim 3, characterized in that: In the step three, the binder is one or more combinations of polyvinylidene fluoride and carboxylated polyvinylidene fluoride.

7. The method for estimating oxygen release of a ternary lithium-ion battery cathode material according to claim 3, characterized in that: In the step three, the conductive agent is one or more combinations of carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene.

8. The method for estimating oxygen release of a ternary lithium-ion battery cathode material according to claim 3, characterized in that: In the step three, the mass ratio of the nickel-cobalt-manganese ternary positive electrode material to the conductive agent and the adhesive in the positive electrode plate is any one of 8:1:1, 90:5:5 and 92:4:

4.

9. The method for estimating oxygen release of a ternary lithium-ion battery cathode material according to claim 3, characterized in that: In the step 3, the drying conditions in the blast drying oven are: 100-130° C., 10-15 hours.

10. The method for estimating oxygen release of a ternary lithium-ion battery cathode material according to claim 3, characterized in that: In step 7, the phase transition chemical reaction equation of the positive electrode material of the ternary lithium-ion battery is: Where M represents Ni x Co y Mn z ; The layered structure can be represented as LiMO2, the spinel structure can be represented as (Li+M)3O4, and the rock salt structure can be represented as (Li+M)O; a represents Li a Remaining lithium content in MO2; b and c represent the amount of oxygen released during the phase transition.